Challenging the patriarchal culture; Feminist critical discourse analysis of the Indonesian environmental heroines - Ernanda, Ernanda (Wacana, Journal of the Humanities of Indonesia, 2023)
This study unveils the representations of women in the documentary film, Tanah Ibu Kami, which depicts women’s movements defending nature from corporations in four islands in Indonesia. It utilizes feminist critical discourse analysis which incorporates critical discourse analysis and feminist studies to disclose perplexing hegemonic power relations. The data in this study are taken from the transcription of the dialogues in the film. Some extracts constructing the representations of women in the film are extracted for further analysis. Interviews were conducted with the film’s producer and female figures. The four themes constructing the representations of women are: (1) women in patriarchal culture, (2) women as leaders in environmental movements, (3) women as symbols, and (4) women’s enthusiasm to protecting nature. The paper concludes that women are challenging traditional gender divisions and leading environmental movements. They have become the symbol of courage, bravery, and sacrifice. They are recognized as the equivalent of Kartini, a renowned Indonesian heroine, for all they have done as defenders of the land. They have raised awareness of the importance of caring relations with nature and spread the ecophilosophies by which humans can live in harmony with nature.